Home - SyGaco, Sonia B. (Silliman Journal, 2022)
This article is focused on Philippine migration; how migrant Filipinos dealt with the challenges of life in their adoptive homeland — America. The characters’ individual journeys from the homeland tothe host country initiated changes in them that ultimately made each become more conscious of being a Filipino. This study presented a discourse on the Filipino identity as well as on identity negotiations by the Filipino migrants in America. Doing menial jobs in America, the first-generation Filipino migrants were often faced with economic difficulties preventing them from making literal ‘return journeys’ to the homeland. Thus, they were reduced to drawing mental images of and maintaining an imaginary bond with their home and people. This was how they negotiated their Filipinoness as well as eased the loneliness they silently endured while trying to survive in their new land. On the other hand, the second-generation Filipino Americans, who practically did not have memories of their homeland, regained their Filipinoness by coming to the Philippines and experiencing their parents’ people and culture. Enriquez’s Sikolohiyang Pilipino (SP) underpins this manner of reintegration. In conclusion, this study demonstrated the “journeying within” of the first-generation migrant Filipinos. These migrants could not afford to fly back home so they had to content themselves with reliving their best memories of their homeland. This was also their means of maintaining their Filipino identity. At the same time, it illustrated the “journeying back” of the new wave of first-generation migrants as well as their children who have already ‘made it’ in America and so they could now make annual pilgrimages to the homeland. Such journeying back to the Philippines was their means of getting in touch and/or coming to terms with their Filipinoness.